2021
DOI: 10.1038/s42003-021-01770-6
|View full text |Cite
|
Sign up to set email alerts
|

Sociality sculpts similar patterns of molecular evolution in two independently evolved lineages of eusocial bees

Abstract: While it is well known that the genome can affect social behavior, recent models posit that social lifestyles can, in turn, influence genome evolution. Here, we perform the most phylogenetically comprehensive comparative analysis of 16 bee genomes to date: incorporating two published and four new carpenter bee genomes (Apidae: Xylocopinae) for a first-ever genomic comparison with a monophyletic clade containing solitary through advanced eusocial taxa. We find that eusocial lineages have undergone more gene fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 66 publications
(120 reference statements)
1
56
2
Order By: Relevance
“…Our dataset afforded a first test of this idea in the wasps. We were surprised to find that the highest rates of gene evolution were detected in the wasp species with the simpler societies rather than the more complex societies; these results are in stark contrast with the findings of a recent study on a range of social complexity in bees 8 where (in keeping with previous studies), rapid gene evolution was most apparent among species with the most complex societies. There are several interpretations of these contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our dataset afforded a first test of this idea in the wasps. We were surprised to find that the highest rates of gene evolution were detected in the wasp species with the simpler societies rather than the more complex societies; these results are in stark contrast with the findings of a recent study on a range of social complexity in bees 8 where (in keeping with previous studies), rapid gene evolution was most apparent among species with the most complex societies. There are several interpretations of these contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
“…Taken together, these results provide evidence that the molecular processes regulating caste differentiation vary depending on the level of social complexity. The finding of more rapid rates of protein evolution in the simpler societies (Supplementary Figure 3c) was unexpected since studies of gene evolution in social bees have found the higher rates of evolution in the more complex societies 8 .…”
Section: Aim 2: How Does Level Of Social Complexity Phylogeny and Life-history Influence The Molecular Basis Of Castes?mentioning
confidence: 89%
See 3 more Smart Citations